Study on the noise reduction methods for a semi-hermetic variable frequency twin-screw refrigeration compressor. (May 2021) - Shen, Jiubing; Chen, Wenqing; Yan, Siyuan; Zhou, Minglong; Liu, Hua
Highlights: Two noise reduction methods together with the theories were introduced. The compressor's flow and sound field simulation models were developed. The noise reduction methods have good effect at speed higher than 4000 rpm. The noise level of an actual compressor was reduced to be lower than 85.5 dBA. Abstract: The semi-hermetic twin-screw refrigeration compressors have been widely applied in middle size refrigeration and heat pump systems. The operation noise of the twin-screw refrigeration compressor is becoming a crucial limitation for their applications. Two noise reduction methods for a semi-hermetic variable frequency twin-screw refrigeration compressor were developed. One is the end face attenuation passage and the other is the discharge pipe damping. The former reduces the gas pulsation amplitude in the discharge chamber which is the main noise source. The discharge pipe damping is comprised of several Helmholtz resonators and is installed in the discharge pipe within the compressor. Methods for the flow field and sound field simulation of the compressor were further proposed to verify the noise reduction effect of each method. Moreover, an experimental study was carried out to evaluate the general effect when the two method were applied in a real compressor. Both simulation results and experimental results demonstrated that both noise reduction methods had good effect. According to the experimental results, the actual operation noise level was no more than 85.5 dBA and the mean noise reduction value was in the range of 5.0 dBA–10.0 dBA when the rotational speed increased from 3000 rpm to 5100 rpm.